PERBANDINGAN PENGATURAN MENGENAI DOKTRI BUSINESS JUDGEMENT RULE DI NEGARA INDONESIA DAN AUSTRALIA: Comparison Of Business Judgement Rule Doctrine Regulation in Indonesia and Australia - Maulina, Arabella Kezia Putri; Yunari, Sri Bakti (Faculty of Law, Universitas Trisakti, 2024)
The Business Judgment Rule Doctrine is a doctrine that is widely applied in common law countries, suchas in Australia which adopted the Business Judgment Rule Doctrine into its positive law since theCorporate Law Economic Reform Program (Corporate Law Economic Reform Program) in 1998.Indonesia itself who are Civil law also apply the Business Judgment Rule Doctrine which is in theDefault case committed by PT Ciremai Prima Mandiri in Decision Number 156/Pdt.G/2013/PN.Jkt.Tim.Based on this, the issues raised are how are the similarities and differences regarding the BusinessJudgment Rule Doctrine between Indonesia and Australia, and how is the Application of the BusinessJudgment Rule Doctrine between Indonesia and Australia between the Default case by PT CiremaiPrima Mandiri in Decision Number 156/ Pdt.G/2013/PN.Jkt.Tim with Mariner Corporations Ltd case.The research was conducted normatively, using secondary data. The results of this study indicatesimilarities in the concepts and objectives of the Business Judgment Rule Doctrine and differences in theelements of the Business Judgment Rule Doctrine between the two countries, as well as showing the form of application of the Business Judgment Rule Doctrine in the default case by PT Ciremai Prima Mandiriin Decision Number 156/Pdt .G/2013/PN.Jkt.Team with Mariner Corporations Ltd case